Interferon-γ-Treated Mesenchymal Stem Cells Modulate the T Cell-Related Chemokines and Chemokine Receptors in an Animal Model of Experimental Autoimmune Encephalomyelitis - Ahmadifard, Reza; Jafarzadeh, Abdollah; Mahmoodi, Merat; Nemati, Maryam; Rahmani, Mehdi; Khorramdelazad, Hossein; Ayoobi, Fatemeh (Drug Research, 2023)
Background Mesenchymal stem cells (MSCs) modulate immune responses, and their immunomodulatory potential can be enhanced using inflammatory cytokines. Here, the modulatory effects of IFN-γ-licensed MSCs on expression of T cell-related chemokines and chemokine receptors were evaluated using an experimental autoimmune encephalomyelitis (EAE) model.Material and Methods EAE was induced in 3 groups of C57bl/6 mice and then treated with PBS, MSCs and IFN-γ-treated MSCs. The EAE manifestations were registered daily and finally, the brain and spinal cords were isolated for histopathological and gene expression studies.Results The clinical scores were lowered in MSCs and IFN-γ-licensed MSCs groups, however, mice treated with IFN-γ-licensed MSCs exhibited lower clinical scores than MSCs-treated mice. Leukocyte inﬁltration into the brain was reduced after treatment with MSCs or IFN-γ-licensed MSCs compared to untreated group (P<0.05 and P<0.01, respectively). In comparison with untreated EAE mice, treatment with MSCs reduced CCL20 expression (P<0.001) and decreased CXCR3 and CCR6 expression (P<0.02 and P<0.04, respectively). In comparison with untreated EAE mice, treatment with IFN-γ-licensed MSCs reduced CXCL10, CCL17 and CCL20 expression (P<0.05, P<0.05, and P<0.001, respectively) as well as decreased CXCR3 and CCR6 expression (P<0.002 and P<0.02, respectively), whilst promoting expression of CCL22 and its receptor CCR4 (P<0.0001 and P<0.02, respectively). In comparison with MSC-treated group, mice treated with IFN-γ-licensed MSCs exhibited lower CXCL10 and CCR6 expression (P<0.002 and P<0.01, respectively), whereas greater expression of CCL22 and CCR4 (P<0.0001 and P<0.01, respectively).Conclusion Priming the MSC with IFN-γ can be an efficient approach to enhance the immunomodulatory potential of MSCs.
Keywords: Experimental autoimmune encephalomyelitis; IFN-γ-licensed MSCs; chemokines; chemokine receptors